Analysis of Clinical Features of Non-steroidal Anti-inflammatory Drugs Induced Kounis Syndrome - Wang, Chunjiang; Fang, Weijin; Song, Liying; Deng, Zhenzhen; Li, Zuojun; Sun, Linli (Frontiers in Cardiovascular Medicine, 2022)
Background Current knowledge of non-steroidal anti-inflammatory drugs (NSAIDs) -induced Kounis syndrome is based on case reports. To investigate the clinical features of NSAIDs -induced Kounis syndrome. Method To collect case reports of NSAID-induced Kounis syndrome by searching Chinese and English databases from establishment to January 31, 2022. Result The median age of the included 45 patients (17 males and 28 females) was 51 years (20-80 years). The most frequently involved NSAIDs were diclofenac (12 cases, 26.7%), mepyridine (7 cases, 15.6%) and aspirin (6 cases, 13.3%). Kounis syndrome mainly occurred within 30 minutes after administration, with a maximum latency of 1m. Chest pain (34 cases, 75.6%), dyspnea (18 cases, 33.3%) and allergic reactions (33 cases, 73.3%) are the most common clinical manifestations, with or without elevated myocardial injury markers and serum tryptase. The electrocardiogram mainly showed ST segment elevation in 30 patients (66.7%). Echocardiography and coronary angiography showed abnormalities in some patients. Forty-four patients (97.8%) have a good prognosis after treatment with steroids, antihistamines, vasodilators. Conclusion The possibility of Kounis syndrome should be considered in the presence of symptoms of coronary artery disease when prescribing NSAIDs. Kounis syndrome can be life-threatening, so it is important to correctly identify and treat Kounis syndrome.